EDUCAÇÃO FÍSICA ESCOLAR NO PRIMEIRO SEGMENTO DO ENSINO FUNDAMENTAL: Contribuições para um Debate - Fabiano Pries Devide (Motrivivência, 2002)
Abstract This essay discusses School Physical Education (PE) in 1st and 2nd grades of elementary school. It presents: i) the impact of Lei de Diretrizes e Bases (LDB) on PE; ii) an analysis of Physical Education’s Parâmetros Curriculares Nacionais (PCNs); iii) who should teach PE in schools; iv) the weaknesses of PE professional undergraduate course for the first four years of elementary school; and v) the school as a less valuable place. The conclusions are the following: (i) PE in the 1st and 2nd grades is out of educational process; (ii) the Physical Education’s PCNs is presented as a “minimum curriculum” that is incompatible with the teacher training for the four years of elementary schools; (iii) the PE professional undergraduate keeps the questions about the first segment besides the educational process, and (iv) the school, as a workplace to the PE teacher, is losing value. Key-words: School Physical Education – Professional Undergraduate – Elementary School.